Status of Ukraine's Eurobond Held By the Russian Federation. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses the status of Ukraine's Eurobond held by the Russian Federation. The bond was acquired by Russia's National Wealth Fund (NWF) pursuant to a decision by the Russian Government to provide assistance to Ukraine. In public statements at the time the bond was issued, Russia's Finance Minister, Mr. Siluanov, explained that assistance was being provided via the NWF because the funds had not been appropriated in the federal budget, ruling out a direct intergovernmental credit. The IMF staff is of the view that the Eurobond is an official claim for the purposes of the IMF's policy on arrears to official bilateral creditors.